Does the internal control system affect the quality of financial statements with LHP BPK as Moderation - Nerotumilena, Tresya; Winarna, Jaka (Proceeding of National Conference on Accounting & Finance, 2025)
The purpose of this study was to analyze the effect of internal audit on the quality of financial statements and examination results. This study uses the qualitative data analysis method by collecting primary data through questionnaires given to 44 respondents from the Indonesian Ministry of Agriculture and descriptive data of LHP BPK-RI in 2021-2023. The results indicate that internal audit plays an important role in improving the quality of financial statements at the Indonesian Ministry of Agriculture in achieving an unqualified opinion. In conclusion, this finding is consistent with evidence showing a significant effect of internal audit on improving the quality of financial statements.